NOTICING HYBRID RECASTS IN TEXT CHAT - Mark J. Oliver (English Review: Journal of English Education, 2016)
This study examined ten EFL learners’ noticing of the corrective nature of a form of text-based SCMC (text chat) feedback that combined a recast of a grammatical error with metalinguistic information. The feedback, termed a hybrid recast, was provided by a native-speaker interlocutor during two text chat activities: a spot-the-difference and picture-ordering task. Data was collected in two ways: analysis of task-based dyadic text chat interaction in which uptake was used as an indicator of learner noticing, and a post-task questionnaire containing questions that identified evidence of learner noticing. Interaction analysis showed that learners responded to almost two thirds of the hybrid recasts with uptake. In addition, every learner provided evidence that they had correctly perceived at least some of the hybrid recasts as corrective in their post-task questionnaire responses.Keywords: Text chat (text-based SCMC - synchronous computed-mediated communication), Corrective feedback, Negative evidence, Recasts, Hybrid recasts, Metalinguistic correction, Uptake, Repair, Noticing